Pan-cancer analyses of classical protein tyrosine phosphatases and phosphatase-targeted therapy in cancer - Wang, Tao; Ba, Xinlei; Zhang, Xiaonan; Zhang, Na; Wang, Guowen; Bai, Bin; Li, Tong; Zhao, Jiahui; Zhao, Yanjiao; Yu, Yang; Wang, Bing (Frontiers in Immunology, 2022)
Protein tyrosine phosphatases function in dephosphorylating target proteins to regulate signaling pathways that control a broad spectrum of fundamental physiological and pathological processes. However, detailed knowledge concerning the roles of classical PTPs in human cancer remains elusive. We comprehensively analyzed the regulatory mechanisms and clinical relevance of classical PTPs in more than 9000 tumor patients across 33 types of cancer. The independent datasets and functional experiments were employed to validate our findings. We exhibited the extensive dysregulation of classical PTPs and constructed the gene regulatory network in human cancer. Moreover, we characterized the correlation of classical PTPs with both drug-resistant and drug-sensitive responses to anti-cancer drugs. To evaluate the PTP activity in cancer prognosis, we generated a PTPscore based on the expression and hazard ratio of classical PTPs. Our study highlights the notable role of classical PTPs in cancer biology and provides novel intelligence to improve potential therapeutic strategies based on pTyr regulation.